DNA alterations in Cd133+ and Cd133- tumour cells enriched from intra-operative human colon tumour biopsies - Diana Cervantes-Madrid; Yvonne Wettergren; Peter Falk; Kent Lundholm; Annika G. Asting (BMC Cancer, 2017)
Abstract Background Tumour stem cells are considered important to promote disease progression, recurrence and treatment resistance following chemotherapy in colon cancer. However, genomic analyses of colorectal cancer have mainly been performed on integrated tumour tissue consisting of several different cell types in addition to differentiated tumour cells. The purpose of the present study was to compare genomic alterations in two cell fractions enriched of CD133+ and CD133−/EpCAM+ cells, respectively, obtained from fresh intraoperative human tumour biopsies. Methods The tumour biopsies were fractionated into CD133+ and CD133−/EpCAM+ cells by immunomagnetic separation, confirmed by immunocytochemistry and Q-PCR. DNA were extracted and used for array comparative genome hybridization (aCGH) after whole genome amplification. Frozen tumour tissue biopsies were used for DNA/RNA extraction and Q-PCR analyses to check for DNA alterations detected in the cell fractions. Results The number and size of DNA alterations were equally distributed across the cell fractions; however, large deletions were detected on chromosome 1, 7 and 19 in CD133−/EpCAM+ cells. Deletions were frequent in both cell fractions and a deletion on chromosome 19p was confirmed in 90% of the patients. Conclusion Isolation of enriched cells derived from tumour tissue revealed mainly genomic deletions, which were not observed in tumour tissue DNA analyses. CD133+ cells were genetically heterogeneous among patients without any defined profile compared to CD133−/EpCAM+ cells.